Cromomicinas isoladas de Streptomyces sp. bra-384 recuperada do zoantídeo Palythoa caribaeorum induzem morte celular imunogênica em melanoma metastático - Florêncio, Katharine Gurgel Dias (2021)
Some first-line cytotoxic chemotherapeutics, for example, doxorubicin, paclitaxel and oxaliplatin induce the activation of the patient's immune system through immunogenic cell death (ICD). Tumor cells subjected to ICD work like a vaccine, releasing damage associated molecular patterns (DAMPs), which act as adjuvants, and tumor neoantigens are recognized as antigens. Induction of ICD is rare, but it produces better and longer-lasting antitumor responses. Advanced metastatic melanoma (AMM) is incurable for more than half of patients. The discovery of ICD inducers against AMM is an interesting drug discovery strategy with high translational potential. Chromomycins (CAs) are molecules produced by bacteria of the Streptomyces genus, which have biological activities such as cytotoxic and antibiotic, being considered promising for application in the pharmacological area. Thus, in this study, the induction of ICD by CA5-8 obtained from Streptomyces sp. BRA384 in murine metastatic melanoma (lineage B16-F10). The sulforhodamine B (SRB) test and the clonogenic assay were performed to assess the antiproliferative effect and survival of B16-F10 cells exposed to CAs. Then, stress and cell death, as well as the release of DAMPs by flow cytometry, immunoblot, real-time PCR and luminescence were evaluated. Regarding the antiproliferative effect by the SRB, the CAs were tested in the range of concentrations from 0.32 to 1000 nM, at the times of 4, 8, 12, 24, 48 and 72 h of incubation. It was observed that CA5 and CA7 presented cytotoxicity at a low exposure time (4h and 8h), respectively, both in the nM range. It was seen that the inhibition of proliferation had concentration and time-dependent effects. Furthermore, CA5-8 completely inhibited the formation of tumor cell colonies after 24 hours of incubation at low concentrations, which ranged from 1 to 500 nM among the CAs. For this test, again there was an emphasis on the potency of CA5 and CA7. It was possible to verify that CA5 100nM, CA6 250nM, CA7 250nM and CA8 500nM and the positive control, doxorubicin (0.6µM), incubated for 24 hours, changed the cell morphology, increasing cells with high granularity and wilt, as well as causing the disruption of the plasma membrane and the fragmentation of DNA. The induction of death by apoptosis induced by CAs was confirmed through the detection of cleaved PARP-1. Autophagy, detected using the orange acridine assay, showed a significant increase in autophagic vesicles by all molecules and by Dox, when incubated for 24h. These data were confirmed by the conversion of the LC3BI protein into II. In assays with specific markers for DAMPs, externalization of CRT on the surface of the plasma membrane and release of nuclear HMGB1 by all molecules was verified. Regarding ATP, it was possible to verify an increase in extracellular ATP only by cells incubated with CA5, when compared to the negative control group. The results of stress and cell death contributed to the establishment of an index of events related to ICD. CA5 presented the highest index and together with Dox continued with the studies. Both CA5 and Dox induced the externalization of ERp57. However, only CA5 was able to induce eIF2a phosphorylation, a crucial factor for the ICD phenomenon to happen. Gene expression of genes related to apoptosis, autophagy and reticulum stress was also evaluated by array PCR, and it was found that CA5 and Dox induced alterations in these genes. Finally, the in vivo vaccination test performed on C57BL/6 showed that CA5 was able to generate a vaccine effect, significantly reducing tumor growth in animals vaccinated with cells pre-exposed to CA5. CA5 is an ICD-inducing molecule. Further studies are needed to assess other potentials and mechanisms of action of this compound, contributing to its possible pharmacological use.